Condição humana como elemento propulsor para ações de integração ensino-serviço: perspectiva de residentes em saúde - Mello, Amanda de Lemos (2020)
This study has as general objective to understand the context of the teaching-service integration actions, made possible from the teaching-educational process in the Multiprofessional Residency Program in Health, as enhancing the training of residents to work in the public health system, under the lenses of Edgar Morin's complexity. Appreciative Research was used, through the development of the 4D Cycle, that is, Discovery, Dream, Design e Destiny. The study was conducted with seven residents linked to a Multiprofessional Residency Program Integrated in the Public Health System located in the state of Rio Grande do Sul, Brazil, from July 2017 to April 2018. The data were produced by the four phases of the 4D cycle, made operational through discussion groups and semi-structured interviews. Data analysis was performed according to Green, Silverman and Denzin and Lincoln and provided the coding, creation of categories and identification of themes. The ethical aspects of the research were met, and the research was submitted to the Ethics Committee on Research with Human Beings and registered at Plataforma Brasil. The results covered three major themes, and in relation to the first theme, actions of teaching-service integration in the Multiprofessional Residency Program in Health, three categories emerged: dimensions of teaching-education, conceptions about teaching-service integration and appreciative actions of teaching-service integration in health residency. As for the second theme, Dreams regarding the appreciative actions of teaching-service integration in the Multiprofessional Residency Program in Health, the categories that emerged were: agreements to strengthen the teaching-service integration actions and the idealized actions of teaching-service integration in the Multiprofessional Health Residency Program. And finally, the third theme, Future projects for teaching-service integration actions in PRMS, comprised two categories: planning of teaching-service integration actions in the Multiprofessional Health Residency Program and possible collaboration networks for the future of the Teaching Service Integration actions in the Multiprofessional Residency Program in Health. The results showed that the context of the teaching-service integration actions goes beyond the standardized elements, but is in a world of affection, responsibility, dialogue, poetry, loveliness, solidarity and ethics, covering the subjectivity of the human condition and dialogical relations. With this, the residents dreamed and planned with the creation of an Appreciative Space, being constituted as a pedagogical space that stimulates the human condition, involving subjective aspects and the production of life. It was concluded that the teaching-service integration actions can be understood as a living, transdisciplinary and interrelated system between individuals present in multiple instances, such as in academia, management, health services and the community. Still, these actions can be influenced beyond agreements, pacts and legal aspects, but understanding the human condition, encompassing subjective elements such as the sensitivity, ethics, creativity and solidarity of dialogical relations, in view of the commitment to the life and health of the population and the public health system.